Congenital (Infantile) Hypertrophic Pyloric Stenosis (IHPS) - AL Hakeem, Basim H; Hanoudi, Basil M; Hanoudi, Basil M; Malik, Hussen (AL-Kindy College Medical Journal, 2006)
Background: Infantile hypertrophic pyloric stenosis affects 0.5 – 3.0 per 1000 live birth and it is the most common surgical cause of vomiting in infancy. Objective: To analyze variable peri-natal factors that may be involved in the etiology of infantile hypertrophic pyloric stenosis. Methods: Over a two year’s period, from January 2000 – December 2001, 31 cases of infantile hypertrophic pyloric stenosis were evaluated for variable peri-natal risk factors in AL-Eskan central child teaching hospital for children. Results: The 31 cases studied were 77.4% males and 48.4% at three weeks of age. And of all cases, 51.6% were breast fed with a blood group (O) being the predominant in 54.8%. Normal vaginal delivery was in 80.6% of cases. All infants 100% had vomiting, and 48.4% of them presented with Jaundice and only 16.1% had constipation. There were no significant correlations between age and pyloric mass size, age and presence of jaundice or between pyloric mass size and the presence of jaundice. Conclusion: Infantile hypertrophic pyloric stenosis is a common condition affecting young infants and its etiology remains unknown, more genetic and environmental factors should be investigated in the future.